Answer:
=![\sqrt[3]{49x^{2} }](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7B49x%5E%7B2%7D%20%7D)
Step-by-step explanation:
We have been given the expression;
7 times x to the two thirds power which can be written mathematically as;
![(7x)^{\frac{2}{3}}](https://tex.z-dn.net/?f=%287x%29%5E%7B%5Cfrac%7B2%7D%7B3%7D%7D)
To express the above expression as a radical, we need to recall that;
![a^{\frac{b}{n}}=\sqrt[n]{a^{b}}](https://tex.z-dn.net/?f=a%5E%7B%5Cfrac%7Bb%7D%7Bn%7D%7D%3D%5Csqrt%5Bn%5D%7Ba%5E%7Bb%7D%7D)
Therefore;
![(7x)^{\frac{2}{3}}=\sqrt[3]{(7x)^{2} }\\\\=\sqrt[3]{49x^{2} }](https://tex.z-dn.net/?f=%287x%29%5E%7B%5Cfrac%7B2%7D%7B3%7D%7D%3D%5Csqrt%5B3%5D%7B%287x%29%5E%7B2%7D%20%7D%5C%5C%5C%5C%3D%5Csqrt%5B3%5D%7B49x%5E%7B2%7D%20%7D)
Answer:
It would be positive(4,4)
Step-by-step explanation:
hope it helps
3/65
is the awnser.good day
Solve your equation step-by-step.
3(x+1)=−2(x−1)−4
Simplify both sides of the equation.
3(x+1)=−2(x−1)−4
Simplify:
3x+3=−2x−2
Add 2x to both sides.
3x+3+2x=−2x−2+2x
5x+3=−2
Subtract 3 from both sides.
5x+3−3=−2−3
5x=−5
Divide both sides by 5.
5x/5 = −5/5
x=−1
Answer: 18m
Step-by-step explanation:
9m + 9
Simplify:
9+9=18
Hence, the answer to 9m + 9 is 18m.